Can an Electronic Money Transaction Raise the Inflation Rate? (Indonesian Pre-Pandemic) - F. Fadli; V. Devia (Финансы: теория и практика)
Along with the rapid growth of technology, payment instruments are also changing. Electronic money is slowly but surely replacing the role of paper money and coins. The emergence of electronic money can provide convenience for consumers, it can lead to an increase in the demand for goods and services that ultimately leads to demand-pull inflation.The purpose of this study is to determine the impact of electronic money transactions (both in natural and in value terms) on inflation growth. By using the Chow Breakpoint Test, Difference-in-Differences and Propensity Score Matching shows that the inflation trend has tended to decline since the Bank of Indonesia launched its national non-cash campaign.By using the ordinary least squares (OLS) method was revealed that an increase in the volume of electronic money transactions in the long-term may affect a decrease in inflation, but not in the short-term. The rate of interest of the Bank of Indonesia, the growth of lending and GDP led to the decline in inflation.It was concluded that the Bank of Indonesia could expand the use of electronic money to manipulate inflation levels in the long-term. The policy that can be implemented by Bank Indonesia is to distribute electronic money infrastructure services more evenly and increase the socialization of the use of electronic money, especially in remote areas.